2022
DOI: 10.3390/cancers14020346
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Acetylation, Cancer Hallmarks and Emerging Onco-Therapeutic Opportunities

Abstract: Acetylation, a reversible epigenetic process, is implicated in many critical cellular regulatory systems including transcriptional regulation, protein structure, activity, stability, and localization. Lysine acetylation is the most prevalent and intensively investigated among the diverse acetylation forms. Owing to the intrinsic connections of acetylation with cell metabolism, acetylation has been associated with metabolic disorders including cancers. Yet, relatively little has been reported on the features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 143 publications
(156 reference statements)
0
19
0
Order By: Relevance
“…For histone acetylation to exert their biological functions, they also need to be combined with specific recognition proteins. Acetylated lysine in a protein will provide a reading site, recruit proteins with special structural domains, affect biological functions such as gene replication, gene transcription, and repair after DNA damage, and jointly participate in the regulation of gene expression ( 8 ). Recognition proteins can contain multiple different recognition domains that cooperate with PTM sites.…”
Section: The Components and Process Of Acetylation System In Cancersmentioning
confidence: 99%
See 3 more Smart Citations
“…For histone acetylation to exert their biological functions, they also need to be combined with specific recognition proteins. Acetylated lysine in a protein will provide a reading site, recruit proteins with special structural domains, affect biological functions such as gene replication, gene transcription, and repair after DNA damage, and jointly participate in the regulation of gene expression ( 8 ). Recognition proteins can contain multiple different recognition domains that cooperate with PTM sites.…”
Section: The Components and Process Of Acetylation System In Cancersmentioning
confidence: 99%
“…Recognition proteins can contain multiple different recognition domains that cooperate with PTM sites. Studies have shown that lysine-containing acetylation modification sites can be specifically recognized by proteins such as bromodomains, dual-PHD finger domains, and YEATS domains ( 8 ).…”
Section: The Components and Process Of Acetylation System In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…The balance of HDACs’ and HATs’ activity in the cell is fundamental for the achievement of the correct cellular function [ 12 ] and, for this reason, these enzymes need to be strictly regulated in the cells ( Figure 1 ). Any mutation or any change in their expression, or in the expression of the genes they regulate, could even lead to tumor development and cause neurological disorders, such as Huntington’s (HD) and Alzheimer’s diseases (AD) [ 13 , 14 ].…”
Section: Hdacs and Hatsmentioning
confidence: 99%